Scene of the cybercrime computer forensics handbook - Shinder, Debra Littlejohn; Tittel, Ed. (Rockland, MA : Syngress Pub., 2002)
"Cybercrime and cyber-terrorism represent a serious challenge to society as a whole."--Hans Christian Kruger, Deputy Secretary General of the Council of Europe Crime has been with us as long as laws have existed, and modern technology has given us a new type of criminal activity: cybercrime. Computer and network related crime is a problem that spans the globe, and unites those in two disparate fields: law enforcement and information technology. This book will help both IT pros and law enforcement specialists understand both their own roles and those of the other, and show why that understanding and an organized, cooperative effort is necessary to win the fight against this new type of crime. 62% of US companies reported computer-related security breaches resulting in damages of $124 million dollars. This data is an indication of the massive need for Cybercrime training within the IT and law enforcement communities. The only book that covers Cybercrime from forensic investigation through prosecution. Cybercrime is one of the battlefields in the war against terror.
Chapter 1: Introduction -- Chapter 2: The Rise of Cybercrime -- Chapter 3: Understanding the Cybercriminal Mindset -- Chapter 4: Understanding Computer and Networking Basics -- Chapter 5: Understanding Network Intrusions and Attacks -- Chapter 6: Understanding Cybercrime Prevention -- Chapter 7: Understanding Windows Security Features -- Chapter 8: Understanding Cybercrime Detection -- Chapter 9: Collecting and Preserving Digital Evidence -- Chapter 10: Building the Cybercrime Case -- Chapter 11: Conclusion.
Includes index.
Keywords: Computer security -- Handbooks, manuals, etc; Computer networks -- Security measures -- Handbooks, manuals, etc; Computer crimes -- Investigation -- Handbooks, manuals, etc; Forensic sciences -- Handbooks, manuals, etc; Electronic books